Wireless Power Transfer Antenna Alignment Using Intermodulation for Two-Tone Powered Implantable Medical Devices - Zhang, Hao (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
10.1109/TMTT.2019.2901674